OBTAINING ACTIVE COMPONENTS (Tа, Rа) of BIMETALLIC CATALYSTS ON γ-Al2O3 AND TiO2 MATRICES - E. S. Kulikova; D. V. Drobot; A. V. Chistyakov; M. V. Tsodikov (Тонкие химические технологии)
Tantalum methylate of general formula Ta2(OMe)10 was synthesized by electrochemical synthesis as a precursor for obtaining oxomethylate complexes of tantalum and rhenium. The complex is used to prepare catalysts in reactions of cross-condensation and reductive dehydration of alcohols. The catalysts are based on γ-Al2O3 and TiO2. Ultradisperse and nanosized TiO2 is obtained by the supercritical fluid technology. The sample is characterized by different methods (DTA, XRD, DSC). It is shown that annealing at 340°C allows obtaining anatase modification of TiO2 with a specific urface of 27.3 sq.m/g which can serve as a matrix for drawing active components of catalysts. It is shown that the Ta-Re/Al2O3 catalyst allows transforming ethanol and mixtures of ethanol with glycerin into aliphatic hydrocarbons C3-C11. A technological scheme for obtaining active components of the catalysts for cross-condensation and reductive dehydration of alcohols is suggested.